Mesurer et nommer la catastrophe : usages politiques des tremblements de terre du 6 février 2023 dans le sud-est de la Turquie - Youenn Gourain; Solène Poyraz (EchoGéo)
The seismic disaster occurring in the southeastern part of Turkey was triggered by an earthquake of magnitude 7.8 at 01:17 (UTC) and a second of magnitude 7.5 at 10:24 (UTC) on Monday, February 6 2023. The population suffers significant human losses and material damage in the area comprising south-eastern Turkey and north-western Syria (2,600 dead on the first day). The attention paid by the media to the failures associated with the constructions cannot summarize the causes of the disaster. This article intends to broaden the understanding of the seismic catastrophe taking place in Turkey by integrating it into a broader spatio-temporal continuum and considering more complex interdependencies.